ANALISIS MEDIAN JALAN TERHADAP KINERJA RUAS JALAN NANI WARTABONE - Bumulo, Ronny; Koem, Ahmad (Universitas Bina Taruna Gorontalo, 2021)
Abstract : The Effect Analysis of the Median Road on the Performance at Nani Wartabone Road Section. The Nani Wartabone Road is a means of transportation that really supports the economic progress of the people of Gorontalo. The need for transportation is increasing. Transportation facilities are also increasingly diverse, including the median road. When the road widening was carried out on the Road, there were a lot of traffic jams, unstable and undirected vehicle speeds that made other drivers and the public uncomfortable. To anticipate this, the Gorontalo Provincial government made a median. The median is designed to reduce accidents, increase comfort, add to the beauty of the road and regulate traffic flow. To determine the effect of the median, we need the average daily traffic data and headway data before the median. This data was obtained from the Public Works Office of Gorontalo Province, data for 2022. From this data, the speed, current and density that occurred were calculated, then compared with survey data during the research that had been analyzed. Based on the data analysis, the median traffic speed is 31.21 km/hour .monday, 31.40 km/hour Tuesday, 31.43 km/hour Thursday and 31.16 km/hour Sunday. The density then after the median becomes 11.15 vehicles/km. It can be said that the media can affect the speed of flow and the average speed of traffic.